Child-caregivers’ body weight and habitual physical activity status is associated with overweight in kindergartners - Hoffmann, Sascha W (BioMed Central, 2014)
BACKGROUND: The aim of this study was to examine whether child-caregivers’, both parents and kindergarten teachers, health parameters (age, weight status, habitual physical activity score) are significantly associated with the risk of overweight in young children. METHODS: We assessed the individual body mass index standard deviation score in a regional cross-sectional health study and matched a representative sample of 434 kindergartners aged 3 to 6-years with their caregivers’ weight and habitual physical activity status. Furthermore, we identified factors associated with the general ability of child-caregivers to identify overweight in children, and the awareness to classify a child within the correct weight category. RESULTS: Our study confirmed most of the known associations between parental anthropometrics and psychosocial factors with childhood overweight and obesity. A significantly higher proportion of boys tended to be overweight or obese (p = 0.027) and parents were more likely to misclassified boys overweight as normal weight (OR: 1.86; 95% CI 1.21-2.86). Adjusted for confounders, logistic regression analysis revealed that kindergarten teachers’ weight status (OR: 1.97; 95%-CI: 1.01-3.83) and habitual physical activity scores (OR: 2.32; 95%-CI: 1.10-4.92) were associated with children’s weight status. CONCLUSIONS: Kindergarten teachers’ weight and habitual physical activity score seem to be new independent risk factors for overweight in kindergartners 3 to 6-years of age. Our results suggest that the psychosocial, non-genetic association of non-parental child-caregivers on children’s weight is relatively high and that the association of non-parental child-caregivers warrants further investigation.